2001
DOI: 10.1111/1468-0297.00599
|View full text |Cite
|
Sign up to set email alerts
|

Income Inequality, Competitive Balance and the Attractiveness of Team Sports: Some Evidence and a Natural Experiment from English Soccer

Abstract: This paper examines the relationship between ®nancial inequality, competitive balance and attendance at English professional league soccer. It shows that while ®nancial inequality among the clubs has increased, competitive balance has remained relatively stable and match attendance appears unrelated to competitive balance. A clearer test of the relationship is suggested by comparison with FA Cup matches. Because income inequality is primarily driven by inter-rather than intra-divisional inequality, the FA Cup … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
108
0
9

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(127 citation statements)
references
References 9 publications
10
108
0
9
Order By: Relevance
“…Resources are allocated on the basis of performance at domestic and international levels. Football economics has been researched as a sub-discipline of professional team sports as argued in Szymanski (2001). The pioneering study of Sloane (1971) provided the first detailed insight of football teams as competitive firms.…”
Section: Introductionmentioning
confidence: 99%
“…Resources are allocated on the basis of performance at domestic and international levels. Football economics has been researched as a sub-discipline of professional team sports as argued in Szymanski (2001). The pioneering study of Sloane (1971) provided the first detailed insight of football teams as competitive firms.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found a positive relation between the variables in just 10 cases (from a total sample of 77), and this relationship existed mostly for small clubs (not for larger ones). Szymanski (2001) also showed that the increased degree of inequality in the revenues earned by small and large clubs did not change the level of competitiveness in the English clubs. The probability of winning or losing a game was not affected by economic recovery.…”
Section: Financial Variables and Sports Performancementioning
confidence: 92%
“…Szymanski (2001) claims that the utility of fans depends on the sporting success of their team. We may agree in general terms with this, but some nuances may be drawn.…”
Section: Quality Of Squad and Attendancementioning
confidence: 99%